Luigi Cosenza, Bernard Rudofsky and Gio Ponti and the Secret of the Mediterranean Sea - Concetta Tavoletta (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2021)
Landscape, cavity, courtyard, skin, pergola are some of the elements of the Mediterranean abacus that architecture tries to transfigure into a single substance but also as a derivation of a great mother, the Mediterranean Sea. However, we can suppose that all these elements come from an idea that acts as a trait d'union, an intuition that made the domestic space of the Mare Nostrum the place of the myth of living: the innovative idea of horizon summarized as the ability of the gaze to observe outward. Gio Ponti, Bernard Rudofsky and Luigi Cosenza are the architects of the materialization of this idea where the horizon is not only found in the relationship with the landscape but is present within the domestic space. In this space full of symbolism and origin, three houses are a body to be vivisected and rediscovered. Casa per Positano... and other shores, Hotel San Michele in Capri, Casa a Procida become autoptic and utopian spaces from which to steal the secret of the Mediterranean Sea.